An investigation into the attitudes of teachers and students at the Hanoi College of Industrial Economics towards speaking activities in the textbook New Headway Pre-intermediate and some suggestions - Nguyễn, Thị Phương Lan (ĐHNN, 2017)
Chapter 1 is intended to give some theoretical background related to speaking skills, textbook and the problems in teaching and learning speaking skills. In chapter 2, the methodology underlying the research is presented. This chapter presents the background information of the subjects of the study, the instruments used to collect the data. Chapter 2 provides an analysis on the current situation of teaching and learning speaking at first year classes at the HCIE; the attitudes of teachers and students at the HCIE towards the speaking skills in ELT; the attitudes of teachers and students at the HCIE towards the speaking skills in the textbook NH Pre and the students' preferences and demands. Chapter 3 focuses on some findings and recommendations about learning and teaching speaking skills based on the textbook NH Pre.